2009
DOI: 10.1177/1753193409352417
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of the types of thumb polydactyly in a middle eastern population: a study of 228 hands

Abstract: Several series have reported the distribution of the types of thumb polydactyly in the Caucasian and Far Eastern populations. No data are available for the Middle East. A total of 196 Saudi patients (228 hands) with thumb polydactyly were reviewed. The most common type was Wassel type IV (33.8%) and the least common was Wassel type I (0.4%). A total of 26 hands (11.4%) did not fit into the classic Wassel types including 18 cases of rudimentary duplications, two cases of thumb triplication, and five cases of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…However, there are differences in the specific proportions of each type reported. The results of this study in southwestern China show that type IV accounts for 39.7% of the affected population, while the proportion reported in another domestic study by Su et al, the Middle East study by Al-Qattan et al, the Japan study by Islam et al, and the UK study by Naasan et al show that type IV accounts for 29.6%, 35%, 33.6%, and 20.9% of the respective populations [ 10 12 ].This is different from our statistical results and may be associated with the sample size. This group of data has a large sample size, similar to the previous reports at home and abroad.…”
Section: Discussionmentioning
confidence: 46%
“…However, there are differences in the specific proportions of each type reported. The results of this study in southwestern China show that type IV accounts for 39.7% of the affected population, while the proportion reported in another domestic study by Su et al, the Middle East study by Al-Qattan et al, the Japan study by Islam et al, and the UK study by Naasan et al show that type IV accounts for 29.6%, 35%, 33.6%, and 20.9% of the respective populations [ 10 12 ].This is different from our statistical results and may be associated with the sample size. This group of data has a large sample size, similar to the previous reports at home and abroad.…”
Section: Discussionmentioning
confidence: 46%
“…The reported case is very rare because it consists of a metacarpophalangeal synostosis and two near-normal distal phalanges. Previously reported cases showed either an additional distal interphalangeal joint [11], a slightly deformed interphalangeal joint [10] or symphalangism in more distal joints of the thumb [9,10,[12][13][14]. Interestingly in all reported cases, metacarpophalangeal synostosis or interphalangeal symphalangism was only found in the radial ray.…”
Section: Discussionmentioning
confidence: 83%
“…In the world literature we only found 14 documented cases of thumb malformations with metacarpophalangeal synostosis or interphalangeal symphalangism (Table 1) predominantly from Asia, specifically Saudi Arabia [9,10], Iran [11], Turkey [12] and Japan [13] indicating a potential genetic background. Al-Qattan [10] reported five patients (2.2%) in his study of 228 hands of which only one (0.4%) was a metacarpophalangeal synostosis. Of these five patients three were previously published by Al-Aithan et al [9] and all showed interphalangeous symphalangism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, The most common associated anomaly: the red arrow highlights the middle phalanx anomalies of little finger. (6,(15)(16)(17)(18). These discrepancies may be related to differences in ethnicity, samples, economic status, education, medical level, environment and diet (3,8,9,14).…”
Section: Discussionmentioning
confidence: 99%